Implementation of Community of Common Destiny Policy through One Belt One Road Strategy as China's Defense Effort - Susilowati, Ida; Cahyani, Mustika; Salsabila, Syarifatunnisa Qothrunnada (UIN Jakarta, 2024)
China is one of the countries that adheres to communist ideology just like the Soviet Union during the Cold War. The failure of the Soviet Union became a lesson for China to re-organise its national defence policies and strategies. This research aims to find out China's strategy for maintaining its country's sovereignty so that it does not experience political degradation like the Soviet Union through the Community of Common Destiny policy. This research applies qualitative research methods with literature study data analysis techniques. The Chinese foreign policy approach analyses China's strategy for maintaining its sovereignty. The results show that one of China's strategies to maintain its sovereignty is by implementing the Community of Common Destiny policy, which is manifested through the One Belt and One Road concept, which is a policy to carry out state development with other developing countries in the face of capitalist economic globalisation through defense lines on land and sea (maritime).